Proposição de método para a elaboração do leiaute em empresas direcionadas para a inovação em produtos - Couto, Cristiano Guimarães (Universidade do Vale do Rio dos Sinos, 2010)
The current world economical scenario demands companies to develop diverse methods, including the ones connected to production systems, efficient in making better their competitiveness in the market. In general, the principles, methods and techniques related to the productive systems improvement come from the automobile industry. In a general setting, the furniture industry has a probable tendency to show a more conservative behavior in relation to the usage of new methods connected to production engineering. The present thesis is set out on this context. The basic idea of this paper is propose a non-specific method to the improvement related to the industrial layout taking the production strategy’s dimensions, particularly the speed, into consideration. In order to develop this method the following elements are going to be used: i) bibliographical review on the topic, ii) in-depth analysis of a high standard furniture industry business study case, iii) the author’s contribution. The results obtained by applying the method are: i) reduction of delivery times, ii) Greater flexibility for the manufacture of new products, iii) improvement in indicators related to product quality. This work will allow reflection on what is postulated in the literature regarding the relation between the layout, production volume and variety of products. Such reflection is an assessment of targeting obtained by applying the method.
Keywords: Indústria moveleira; Inovação em produtos; Competitividade; ACCNPQ::Engenharias::Engenharia de Produção